Reconstruction Of Ppat Regulations In The Context Of National Agrarian Law Harmonisation - Noor, Aslan; Rangkoly, Mavelda R.; Poltica M, Refizma; Putry, Bani Amella Maha; Ghaida, Deyna Shafa; Aulia, Puspa Hygea; Habibie, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Land Deed Officials (PPAT) play a central role in the land registration system in Indonesia, functioning as the front line in ensuring legal certainty regarding land ownership rights. However, the regulations governing the position and authority of PPATs are currently still partial and not fully in line with the spirit of the Basic Agrarian Law (UUPA). This condition gives rise to various legal problems that have implications for the emergence of land disputes and hinder the goal of national agrarian law unification. This article examines the urgency of reconstructing PPAT regulations as a strategic step towards harmonising agrarian law in Indonesia. Through a juridical-normative approach, this article analyses the disharmony in existing regulations and offers a comprehensive reconstruction framework, covering the aspects of authority, guidance, supervision, and accountability of PPATs. This reconstruction is expected to strengthen the position of PPAT as professional and integrity public officials, as well as accelerate the realisation of an agrarian legal system that is fair and has legal certainty.